Utilization of Polydioxanone Plate for Endoscopic Anterior Skull Base Repair: Operative Technique and Long-Term Cohort Outcomes - Gutierrez III, Jorge A.; Soler, Zachary M.; Larrew, Thomas; Chapurin, Nikita; Wessell, Jeffrey E.; Schlosser, Rodney J.; Vandergrift III, W. Alexander (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objective The purpose of this study is to report the technical procedure and our experience using a polydioxanone suture (PDS) plate with dural substitute as part of a fully resorbable gasket seal technique to repair anterior skull base defects.Methods A series of patients undergoing anterior skull base reconstruction utilizing our resorbable gasket seal technique from January 2014 to July 2022 was reviewed.Results A total of 155 patients were included. Nine (5.8%) of the included patients developed postoperative cerebrospinal fluid (CSF) leaks requiring reoperation. There were no cases of intraoperative cranial nerve injury or internal carotid artery injury. A total of 103 (66.5%) patients were observed to have an intraoperative CSF leak, including 57 low-flow leaks and 46 high-flow leaks; 1 of 57 (1.8%) patients with low-flow leaks and 8 of 46 (17.4%) patients with high-flow leaks developed a postoperative CSF leak. During the first 3 years that this technique was utilized at our center for the management of high-flow intraoperative CSF leaks, postoperative CSF leaks were documented in 4 of 12 (33.3%) patients, in comparison to 4 of 34 (11.8%) in the following years.Conclusion PDS plate reconstruction confers several advantages and can be used in a diverse set of operative scenarios in conjunction with other reconstruction options. There appeared to be an associated learning curve as surgeons at our center gained experience with this new technique. Our findings show that the PDS plate reconstruction is safe and effective in repairing the skull base.
Keywords: anterior skull base reconstruction; endoscopic skull base; polydioxanone plate; gasket seal